A techno-socio-economic approach to the management of exposure to formaldehyde in indoor air, evidence from China. Issue 4 (September 2019) - Khalili, N R; Nguyen, L V; Wang, Y; Murad, S; Cheng, W; Kumiega, A
Abstract: The United Occupational Safety and Health Administration (OSHA), and World Health Organization (WHO) have clearly demonstrated that indoor exposure to organic gases such as Formaldehyde could cause both chronic and acute health problems ranging from irritation of the eyes, nose, and throat to headaches, dizziness, fatigue, respiratory diseases, heart disease, and cancer. Formaldehyde is a common and persistent indoor air pollutant that can virtually be found indoor and particularly in most of the existing and new homes and buildings in either developing or developed countries. The main goal and objectives of this study are to (a) understand and map socio-techno-economic motives behind having this health risk problem in built environments, and (b) develop sustainable strategies for managing exposure to Formaldehyde in indoor living. Utilizing data collected in a Case study in China suggested that exposure to formaldehyde in indoor environment is primarily a result of: (I) lack of societal awareness of the health risks associated with exposure to indoor air pollutants and effectiveness of the existing technologies, (II) weaknesses in building/architectural design and furnishing, and (III) absence of proper strategic models and programs for exposure assessment and design of instruments that could properly educate public about both the exposure risks and benefits of utilizing indoor air pollution control technologies.